Genetic modulation of stroke in children with sickle cell anaemia - Silva, Marisa (2020)
Sickle cell anaemia (SCA) is an autosomal recessive genetic disease that leads to the synthesis of haemoglobin S (HbS). The pathophysiology of the disease is centred on HbS polymerization inside the red blood cells, which become sickle-shaped (SSRBCs), rigid, viscous and adherent-prone to the vascular endothelium, favouring the occurrence of chronic haemolysis and vaso-occlusion. The main vascular problems of SCA arise from several pathways including endothelial dysfunction and nitric oxide (NO) metabolism. Children with SCA have a much higher risk (11% by age 20 years) of developing stroke or silent cerebral infarcts (up to 37%) than the general paediatric population. Abnormal interactions between SSRBCs and the cerebral arterial endothelium lead to endothelial injury, vaso-occlusion and tissue ischemia and result in cerebral vasculopathy (CVA) through a yet unknown pathophysiological mechanism. Current risk screening strategies rely mainly on imaging techniques (transcranial Doppler ultrasonography and magnetic resonance imaging) and children with altered results undergo regular blood transfusion and/or hydroxyurea therapy to reduce stroke risk/recurrence. However, we need more specific/sensitive biomarkers for stroke prediction/prognosis. Genetic modulators may be paramount in SCA pathophysiology and in CVA severity. They include variants in VCAM1 (endothelial dysfunction), ITGA4 (cell-cell adhesion), and NOS3 (nitric oxide metabolism. The main goals of this work are: a) improve the knowledge on the genetic architecture of paediatric cerebral vasculopathy in SCA; b) assessing the consequences of those genetic variants on gene expression/protein function; c) identify genotypic/phenotypic markers of SCA sub-phenotypes; and d) analyse their potential as genetic modulators of disease severity. This would be crucial in assessing potential pharmacological targets specifically aimed to the vascular system and instrumental for the design of novel preventive, prophylactic or therapeutic strategies.